Patch Testing Tips Recommendations from the ICDRG - Lachapelle, Jean-Marie.; Bruze, Magnus; Elsner, Peter U.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book is a compendium of tips on many different aspects of patch testing based on the recommendations of the International Contact Dermatitis Research Group (ICDRG), which is the reference group for all dermato-allergologists. It is intended to complement the book Patch Testing and Prick Testing: A Practical Guide by J.-M. Lachapelle and H. Maibach, which is an official publication of the ICDRG now in its third edition. Among the wide variety of topics covered are pitfalls, legal aspects, patch testing with ultrasonic bath extracts, the role of patch testing in occupational contact dermatitis and atopic dermatitis, semi-open tests, the implications of a negative test, patch testing validity, selection of extra allergens and patch testing in the tropics. Many illustrations are included and all information is completely up-to-date. This book will be of value to all practicing dermatologists.
The benefit of Patch Testing with Ultrasonic Bath Extracts in Special Cases -- How to Manage Occupational Contact dermatitis -- Patch Testing and Atopic Dermatitis -- Pitfalls -- Legal Aspects -- Updating semi-open tests -- Patch Testing -- Do’s and Dont’s in Patch Testing -- Prick Testing -- When Patch Tests are Negative -- Patch testing validity -- Assessment of the Clinical Relevance -- How to Select Extra-Allergens – or Problematic Allergens -- Patch Testing in the Tropics -- Making a Diagnosis. .
Keywords: Dermatology; Allergy; Dermatology; Allergology